WUJUD KEBUDAYAAN JEPANG DALAM "SENANDUNG OMBAK" KARYA YUKIO MISHIMA - Mujianto, Gigit (Jurnal Bestari, 1992)
It is interesting enough to study Japan and Japanese. They lived in a long "nightmare" after The Second World War. If you seen "The Day After", you can imagine how damage that country was. IN the recent times, however, they got up and passed many countries as the "king" of world economic order. The background of their achievments cannot be separated from their culture and literature. One of the monumental literatures s written by Yukio Mishima.